Mechanical-Physical Properties Characterization Of Alternative Materials For The Application In Highway Guardrail - Mohd Hafni, Aidil Azwadi (Universiti Sains Malaysia, 2022)
The highway guardrails have been the essence of safety for road users. However, there have been several issues reported regarding the current material used for the highway guardrail applications. The issues highlighted are regarding the long-time performance of the materials and also the stolen parts of the highway guardrails which is the packers. Therefore, alternatives material to replace the current galvanised steel material have been studied which are two types of ethylene vinyl acetate polymer, EVA (A) and EVA (B) and also a glass fibre reinforced polymer, B3WG6. The scope of study is to characterize the physical and mechanical properties of these materials. These materials are subjected to 5 tests which are density measure, scanned electron microscopy, thermogravimetric analysis, nanoindentation test, and also tensile test. The standards for the tests are configured through the literature reviews. The results from the test shows that EVA (B) has high probability to be considered as an alternative material for the highway guardrail packers due to its tensile strain property. However, simulation and demonstration needed to be done with a proper prototype in the future for the development of this study.